PEMBINAAN PEDAGANG TAHU DI PASAR BADUNG MENGENAI BAHAYA PENYALAHGUNAAN FORMALIN - Sut iari. N K.; Utami Dwipayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2011)
Formaldehyde is an uncolored substance with very strong odor, and is usually added by methanol by 15% as preservative. The misuse of this substance is strongly banned by the governance. Formaldehyde is sometimes found in raw food such as fish, tofu, fresh noodle and the likes. Tofu product is often sold in traditional market as well as supermarket such as at Badung and Kumbasari markets. This community service program aimed to train the tofu retailer regarding the misuse of formaldehyde (the danger and health effect). This activity was held on 19 and 21 October 2010, and there has been an informal approach to the tofu retailers at Badung and Kumbasari market at 4 October 2010. The informal approach was intended to find out the respondents agreement to join the program. The pre test questionnaire on food additive substance, danger of formaldehyde, health effects and physical sign on food with formaldehyde was distributed to all respondents beforehand. Those questionnaires were aimed to identify the knowledge level of tofu retailers regarding the formaldehyde misuse. Besides, qualitative test was also conducted on two tofu retailers (randomly selected) in Badung market using chromathpate acid at Laboratory of Faculty of Agriculture Technology. The result showed that respondents at Badung and Kumbasari market have been tofu retailer for at least 5 years and considered as a long period. Their knowledge (100%) is considered low regarding the danger of formaldehyde misuses. Based on qualitative test on the tofu samples, formaldehyde in the samples were negative. This indicates that tofu sold at Badung and Kumbasari markets is safe to consume. It is recommended that it is better to do regular assistance for tofu retailer through counseling.